PEMBERIAN RESTITUSI DAN KOMPENSASI KORBAN TINDAK PIDANA DALAM SISTEM PERADILAN DI INDONESIA - Rahmi Erwin; Andi Desmon; Rina Rahma Ornella Angelia (Ensiklopedia of Journal, 2023)
Article 27 paragraph (1) of the 1945 Constitution states that "all citizens have the same position before law and government and are obliged to uphold law and government with no exceptions. This provision becomes a legal umbrella for victims of criminal acts to obtain guarantees for the protection of their rights. Victims of crime are the most disadvantaged subjects if they become victims of crime, the losses suffered either physically, psychologically, materially or non-materially. The justice system is required to be able to provide protection for victims of criminal acts, this protection can be provided through the provision of restitution or compensation. In positive law in Indonesia, various protections for victims of criminal acts have been regulated, such as in the provisions of statutory regulations, namely the 1945 Constitution, which can also be seen in the Criminal Code, KUHAP, Civil Code, Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons, Government Regulation Number 43 of 2017 concerning the Application of Restitution for Children who Become Victims of Crime and Supreme Court Regulation Number 1 of 2022 concerning Procedures for Completing Applications and Granting Restitution and Compensation to Victims of Crime. This provision is intended to change the paradigm that the orientation of protection is not only to the interests of the perpetrators, but also to protect the victims. So that every victim gets the right to protection and guarantees of obtaining restitution and compensation.Key Words: victim, restitution, compensation.